Religiositas sebagai Moderating Variabel Perilaku Konsumsi Rumah Tangga Muslim - Bawono, Anton (Program Pascasarjana UIN Sunan Ampel Surabaya, 2014)
The main objective of this study is to analyze the influence of the religiosity variable as a moderating variable towards the influence of the future income and wealth expectation on stimulating the consumption behavior, and future prospects. The research design used in this study is a survey method. This study is based on the primary data obtained from the respondents in the field observation. The analysis tool is quantitative. In order to answer the research objectives and hypotheses, the study uses multiple regression analysis. To view the suitability of the multiple regression equation model used, a statistical test and classical assumption test are conducted. The analysis indicates that the religiosity variable influences the variable determining consumption. The variable of expected income, an expectation of liquid wealth one period ahead, affects current consumption, which is driven by religiosity. There is a new aspect of this study that is not found in the previous studies, i.e. that the religiosity variable becomes the moderating variable of the variables of income and liquid wealth expectations of future periods, which influence the current consumption behavior. It means that of the variables investigated and concluded so far as those determining consumptions behavior, there is another variable, namely religiosity, which has a more dominant effect in determining consumption behavior.